2007
DOI: 10.1007/s10162-006-0061-8
|View full text |Cite
|
Sign up to set email alerts
|

Tonotopic Distribution of Short-Term Adaptation Properties in the Cochlear Nerve of Normal and Acoustically Overexposed Chicks

Abstract: Cochlear nerve adaptation is thought to result, at least partially, from the depletion of neurotransmitter stores in hair cells. Recently, neurotransmitter vesicle pools have been identified in chick tall hair cells that might play a role in adaptation. In order to understand better the relationship between adaptation and neurotransmitter release dynamics, short-term adaptation was characterized by using peristimulus time histograms of single-unit activity in the chick cochlear nerve. The adaptation function r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
3
17
2
Order By: Relevance
“…As CF increased, adaptation also increased, as measured by a decrease in with duration of stimulation. This was consistent with previous findings (Crumling and Saunders, 2007). The adapted spike-count variance, , was only slightly higher than the initial and was not significantly different at the lowest frequency range (Fig.…”
Section: Spike-count Reliability Decreases After Neural Adaptationsupporting
confidence: 93%
See 3 more Smart Citations
“…As CF increased, adaptation also increased, as measured by a decrease in with duration of stimulation. This was consistent with previous findings (Crumling and Saunders, 2007). The adapted spike-count variance, , was only slightly higher than the initial and was not significantly different at the lowest frequency range (Fig.…”
Section: Spike-count Reliability Decreases After Neural Adaptationsupporting
confidence: 93%
“…9A). Interestingly, at progressively lower frequencies, the time course of spike-rate adaptation slows (Crumling and Saunders, 2007). Thus, over 35 ms, there is a smaller change in the mean spike count (Fig.…”
Section: Spike-count Reliabilitymentioning
confidence: 90%
See 2 more Smart Citations
“…Previous studies have demonstrated that the time course of spike rate adaptation of auditory nerve fibers (ANFs) during pure tone bursts is related to neural CF (Westerman and Smith, 1985;Crumling and Saunders, 2007). A similar relationship was observed in the adaptation to sound level statistics examined in the current study.…”
Section: Adaptation Time Constants Vary With Neural Cfsupporting
confidence: 83%